2014
DOI: 10.1177/0300060513516287
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxonase lactonase activity, inflammation and antioxidant status in plasma of patients with type 1 diabetes mellitus

Abstract: Objectives: To investigate paraoxonase-1 (PON 1 ) lactonase activity, myeloperoxidase (MPO) activity (as a marker of inflammation) and antioxidant status in plasma of patients with type 1 diabetes mellitus. Methods: Whole blood and plasma samples were collected from patients with diabetes and healthy control subjects. PON 1 lactonase and MPO activities and total antioxidant capacity (TEAC) were determined in plasma. Glycosylated haemoglobin (HbA1c) was quantified in whole blood. Results: Plasma PON 1 lactonase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
3
7
0
1
Order By: Relevance
“…In this study, we found that serum paraoxonase, arylesterase and lactonase activities are decreased in STZ-induced diabetic rats. These findings are also in agreement with the previous experimental [11,14,15] and human [16][17][18] studies of diabetes mellitus. We also found that there was no significant difference between the decrease percent of these serum enzyme activities.…”
Section: Paraoxonase Activitysupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, we found that serum paraoxonase, arylesterase and lactonase activities are decreased in STZ-induced diabetic rats. These findings are also in agreement with the previous experimental [11,14,15] and human [16][17][18] studies of diabetes mellitus. We also found that there was no significant difference between the decrease percent of these serum enzyme activities.…”
Section: Paraoxonase Activitysupporting
confidence: 93%
“…It has been shown that PON1 prevents the development of atherosclerosis by protecting LDL against to oxidation and reducing macrophage foam cell formation [10]. Serum PON1 protein levels and paraoxonase, arylesterase and lactonase activities have shown to be decreased in diabetes [11][12][13][14][15][16][17][18] and PON1 has reported to be a…”
Section: Introductionmentioning
confidence: 99%
“…It was evidenced by negative correlation of Castelli Index 1 with PON-1(L) activity showed in the groups of non-smoking and smoking AP patients. A decrease in PON-1 activities can be a result of HDL dissociation from PON-1 molecule, its oxidation and increase in lipid peroxidation products concentrations under oxidative stress conditions as reported in other papers 46,47. This thesis seems to be confirmed in our study by the strong correlations of PON-1 activities with HDL concentration and negative association of HDL and MDA concentrations in the groups of AP patients.…”
Section: Discussionsupporting
confidence: 91%
“…Despite being at increased risk of dyslipidaemia, patients with type 1 diabetes commonly demonstrate elevated—rather than reduced—levels of HDL-c. Multiple studies have reported the presence of multiple dysfunctional properties to these particles, however, including reduced cholesterol efflux capacity [93, 94], reduced PON-1 activity [95], increased MPO activity [96], and decreased levels of S1P [97]. These modifications appear to be independent of HbA1c [93], and may at least partially explain the increased risk of CVD in patients with the highest HDL-c levels [98].…”
Section: Hdl Function In Clinical Populations: Implications For Cvd Riskmentioning
confidence: 99%